MODERN ISLAMIC BOARDING SCHOOLS AS PILLARS OF ISLAMIC EDUCATION IN RIAU - Muhammad Rayfansyah; M. Iqbal Indraji; Ellya Roza (Indonesian Journal of Education (INJOE), 2025)
Islamic education in Riau has a long history rooted deeply in the culture and traditions of Malay society. Islamic boarding schools (pesantren), as the oldest Islamic educational institutions, have played a strategic role in shaping the character, morals, and Islamic identity of the community. This study aims to examine the development of pesantren in Riau from historical, social, and cultural perspectives, as well as to analyze the differences between traditional and modern pesantren in addressing contemporary educational challenges. This study employs a library research method by collecting data from literature, journals, and other written sources. The results show that traditional pesantren focus on education based on classical Islamic texts (kitab kuning) and spiritual values, while modern pesantren integrate religious and general curricula with the utilization of technology. This adaptation enables pesantren in Riau to preserve Islamic values while simultaneously functioning as relevant social institutions in the era of globalization. This study affirms that modern pesantren in Riau serve as an important pillar in strengthening Islamic education that is moderate, competitive, and rooted in local wisdom.